Ecological Character Education for Sustainable Road Development: Strategies for Integrating Green Infrastructure in Indonesia - Anwar Asihinggalih Antiarini; Harsuko Riniwati; Fitri Candra Wardana (AL-ISHLAH: Jurnal Pendidikan, 2026)
Road infrastructure development plays a crucial role in improving regional connectivity and economic growth; however, its implementation continues to rely predominantly on conventional gray infrastructure that often neglects ecological sustainability. Although previous studies have extensively examined green infrastructure from engineering and environmental perspectives, limited attention has been given to the educational processes through which ecological character can be developed among infrastructure stakeholders. This study investigates how ecological character education can strengthen environmentally responsible road infrastructure planning. Specifically, it aims to (1) examine the educational dimensions of ecological character among stakeholders involved in road development, (2) identify the internal and external factors influencing ecological character development, and (3) formulate education-based strategies using SWOT analysis. A descriptive-analytical mixed-methods case study was conducted along the Kepanjen–Pagak Road Section, Malang Regency, Indonesia. Data were collected through interviews, field observations, questionnaires, and document analysis involving government officials, planning consultants, academics, infrastructure practitioners, and community representatives selected through purposive sampling. Qualitative data were analyzed thematically, while quantitative data were examined using the Internal Factor Analysis Summary (IFAS), External Factor Analysis Summary (EFAS), SWOT, and Quantitative Strategic Planning Matrix (QSPM). The findings reveal that ecological character development is shaped by ecological literacy, environmental values, institutional commitment, stakeholder collaboration, and participatory planning, but remains constrained by conventional gray infrastructure practices, weak inter-agency coordination, and limited environmental integration in planning. The IFAS score of 2.72 and EFAS score of 2.82 positioned the study in Quadrant I, indicating strong internal capacity and favorable external opportunities to implement proactive education-oriented strategies. QSPM analysis further identified the Strength–Opportunity (SO) strategy as the highest-priority alternative for integrating ecological character into sustainable road governance. This study contributes to the literature by extending ecological character education beyond formal educational settings into infrastructure governance and professional practice. It also proposes an education-based strategic framework that supports stakeholder capacity building, sustainability competencies, and environmentally responsible infrastructure planning within the broader context of Education for Sustainable Development (ESD).